Internalisasi Nilai-Nilai Pendidikan Ki Hajar Dewantara dalam Kegiatan Tematik Tujuh Poe Atikan Purwakarta di Sekolah Dasar - Enjang Sarip Hidayat; Dian Rini Handayani; Andi Saleh; Ricky Yoseptry; Miftahul Malik (STKIP PGRI SITUBONDO, 2025)
This research is motivated by the formation of national character and civilization, as emphasized by Ki Hajar Dewantara (KHD) that education is a place to sow the seeds of culture (Dewantara, 1961). This research uses a qualitative approach with a case study type. The qualitative approach was chosen because it aims to gain a deep and descriptive understanding of the process of internalizing Ki Hajar Dewantara's educational values ​​in the specific context of the Tujuh Poe Atikan Purwakarta program at SDN Babakansari. The case study was applied to focus the study on one location and a unique program intensively, thus producing rich and comprehensive data. The process of internalizing Ki Hajar Dewantara's educational values ​​in the Seven Poe Atikan Purwakarta thematic activity at SDN Babakansari was carried out through the harmonization of the role of teachers as Pamong who implemented the trilogy Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karso, and Tut Wuri Handayani in every daily theme, starting from instilling a nationalist attitude (Ajeg Nusantara) to spirituality (Nyucikeun Diri). This program provides a space for Independent Learning (Merdeka Belajar), which is directed at fostering character development based on local Sundanese wisdom. Despite challenges in consistent implementation, this thematic program has succeeded in becoming a contextual and sustainable medium for guiding students to achieve the life skills and noble character envisioned by Ki Hajar Dewantara.